Strategi Writing in the Here and Now untuk Meningkatkan Kemampuan Siswa Menulis Teks Rekon di SMA Pangeran Antasari, Medan - Nasution, Ayu Wandani; Pohan, Jusrin Efendi; Perangin-angin, Esra (Jurnal Simki Pedagogia, 2024)
This research was motivated by the low ability of students in writing recon texts. This is because learning still dominates theory over practice, so that students are only able to understand the theory of recon texts, not able to write recon texts. One learning strategy that is believed to be able to improve student learning outcomes is the writing in the here and now strategy for students in writing class X recon texts at Pangeran Antasari High School. This research aims to describe the process and results of implementing the writing in the here and now strategy in improving students' skills in writing recon texts. This type of research is qualitative descriptive research that describes events or phenomena systematically. The data for this research is in the form of 24 student essays. The data analysis technique used is a test technique, namely students are asked to write a recap text. This research shows that the writing in the here and now strategy is very effective in improving students' ability to write recon texts for class X SMA Pangeran Antasari Medan as evidenced by the students' writing. The writing in the here and now strategy also makes the learning atmosphere more active and enjoyable for students by providing collaboration between students.